Lady of the English - Chadwick, Elizabeth, 1957- (Sourcebooks Landmark, 2011)
Queen Adeliza is married to a warrior who supports Stephen, grandson of the Conqueror, while her stepdaughter, Empress Matilda, will let no one, not even Stephen himself, stand in the way of her inheritance.